Statistical Analysis of the Effect of Portland Cement Mortars' Performance Containing Glazed Ceramic Waste - Tepecik, A.; Altin, Z. G. (ACADEMIC PUBLICATION COUNCIL, 2014)
The purpose of this study is to investigate the reusability of waste from tile manufacturing as an alternative material to natural pozzolan (NP) - trass. Chemical and physical analyses of the binary components of Portland Cement (PC42.5N), NP, and Glazed Ceramic Waste (GCW) were conducted. The strength values of PC42.5N were measured by adding trass and GCW at various weight ratios by cement weight (5, 10, 20, 30, 40%) to curing periods of 2, 7, 28, 56, and 90 days. The results show that the final setting time of cement pastes is generally accelerated when NP was replaced with cement. Based on the test results, there are good compressive strength values with less than 15% concentrations of waste materials. A decrease in strength was observed at increased concentrations of waste materials. Statistical results show that GCW is an alternative to trass as a supplementary cementing material (SCM) with PC42.5N. Using less than 15% of GCW as an additive was observed to be an alternative to trass. The results also indicated that there is an increase in compressive strength when up to 10% of NP is added, compared with that of the control concrete and with trass.
Keywords: Statistical Analysis; Reusability of Waste; Glazed Ceramic Waste; Fischer Distribution; Analysis of Variance (ANOVA); NATURAL POZZOLAN; COMPRESSIVE STRENGTH; SILICA FUME; CONCRETE; Engineering